2022
DOI: 10.1371/journal.pone.0269885
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of immunoglobulin G antibodies against SARS-CoV-2 in Cyprus

Abstract: Monitoring the levels of IgG antibodies against the SARS-CoV-2 is important during the coronavirus disease 2019 (COVID-19) pandemic, to plan an adequate and evidence-based public health response. After this study we report that the plasma levels of IgG antibodies against SARS-CoV-2 spike protein were higher in individuals with evidence of prior infection who received at least one dose of either an mRNA-based vaccine (Comirnaty BNT162b2/Pfizer-BioNTech or Spikevax mRNA-1273/Moderna) or an adenoviral-based vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Ali et al, report higher IgG, IgA, and neutralizing antibodies in the vaccinated with prior infection [24]. Similar results were also reported by Demonbreun et al and Pantelidou et al, with higher values of median IgG and neutralization rate as compared to the non-infected patients [25], [26].…”
Section: Discussionsupporting
confidence: 70%
“…Ali et al, report higher IgG, IgA, and neutralizing antibodies in the vaccinated with prior infection [24]. Similar results were also reported by Demonbreun et al and Pantelidou et al, with higher values of median IgG and neutralization rate as compared to the non-infected patients [25], [26].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, another study on the efficacy of vaccination in adults showed that among vaccinated individuals with prior evidence of infection, there were no significant differences in IgG levels between males and females across all age groups ( 22 ). Another study on seroprevalence of IgG antibody against SARS-CoV-2 conducted in Cyprus showed that, without evidence of prior infection, anti-spike IgG antibodies were detected after injection of 2 doses of mRNA vaccines in 91.2% participants, while antibody levels showed a decrease at 120 days after vaccination ( 23 ).…”
Section: Resultsmentioning
confidence: 99%